Antimicrobial effect of the hydrodynamic action of 1 and 2.5% sodium hypochlorite in infected root canals - Valéria Teixeira de Andrade; Orlando Aguirre Guedes; Lucas Rodrigues de Araújo Estrela; Luiz Evaristo Ricci Volpato; Alexandre Meireles Borba; Cyntia Rodrigues de Araújo Estrela (Revista Sul-Brasileira de Odontologia, 2021)
The mouth has various microorganisms that can live in the free form, called planktonic, or in organized groups, called biofilm. Objective: To determine the antimicrobial effect of the hydrodynamic action of sodium hypochlorite (NaOCl) on the biofilm of Enterococcus faecalis with different of maturity biofilms. Material and methods: Sixty bovine incisors were decoronated, prepared, inoculated with E. faecalis, and examined after 7, 14, 28, and 60 days. Eppendorf tubes were connected to the coronal portion of the root. Urethane hoses were attached to the tubes and to the entrance of a peristaltic pump. The test irrigating was 1 and 2.5% NaOCl solutions that circulated at a constant flow of 50 mL min-1 for 20 min. Samples from the root canals were collected before and after the use of NaOCl solutions, and the bacterial growth was analyzed using turbidity of culture medium followed by ultraviolet spectrophotometry. Results: All protocols showed a significant reduction of the optical density of the culture medium (p < 0,05). However, none of them promoted the complete elimination of E. faecalis. Conclusion: The hydrodynamic action of 1 and 2.5% NaOCl solutions reduced the microorganisms of the biofilm, but it was not sufficient to inactivate E. faecalis in different of maturity biofilms.